(untitled) (Journal of Academic Research, 2023)
P.aeroginosa is one of the most serious pathogens of infections, it produces Metallo-β-lactamases which is a diverse set of enzymes that catalyze the hydrolysis of a broad range of β-lactam drugs including carbapenem. Contamination with this pathogen remain one of the most serious problems in Hospitals, especially with the intensive exposure to antibiotics, where many studies reported that P.aeroginosa has developed resistance thus cause high rate of mutations. This will complicate the situation and improve the maximum limit for possible antibiotic treatment (14; 29). Alternatively, diagnosis efficiency will lead to treatment failure and complicate the situation, therefore it is important to introduce new tools to the followed routine identification procedures of P. aeruginosa at Libyan hospitals.